PERKEMBANGAN KUALITAS PENDIDIKAN PEREMPUAN DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH KHAIRIYAH HASYIM SEBLAK (STUDI PEMIKIRAN NYAI KHAIRIYAH HASYIM 1908 – 1983) - Muhammad Ainul Yaqin; Siti Rofi’ah (JURNAL ILMIAH NUSANTARA, 2025)
The importance of Women’s Education is a study that really need to be discussed, because education is a very crucial need in the life of a state society. Someone who has knowledge is certainly very different from someone who does not have knowledge and is educated. In islam it self, men and women are ordered to be knowledeable, and to get quality education, someone is needed who is able to create a quality educational environment as well. Researchers focused this reseacrh into 2 focuses, namely (1) How is Nyai Khairiyah Hasyim’s Thought on Women’s Education? (2) How is Nyai Khairiyah Hasyim’s Thought in Developing the Quality of Women’s Education in Salafiyah Syafi’iyah Khairiyah Hasyim Seblak Islamic Boarding School ? . To answer the 2 research focuses, researchers used qualitative approach method with a type of historical research with data collection techniques through interviews and documentation which were the analyzed with data reduction techniques and will be presented and concluded. Nyai Khairiyah Hasyim who is daughter of KH Hasyim Asy’ari was born and grew up in Tebuireng Islamic Boarding School environment received direct education from KH Hasyim Asy’ari making her a critical person and concerned about the importance of education, especially for women, Nyai Khairiyah Hasyim tried to develop aspects of women’s personality and skills by establishing formal school and developing a gender quality-based curriculum.